2011
DOI: 10.5194/acp-11-13287-2011
|View full text |Cite
|
Sign up to set email alerts
|

The isotopic composition of methane in the stratosphere: high-altitude balloon sample measurements

Abstract: Abstract.The isotopic composition of stratospheric methane has been determined on a large suite of air samples from stratospheric balloon flights covering subtropical to polar latitudes and a time period of 16 yr. 154 samples were analyzed for δ 13 C and 119 samples for δD, increasing the previously published dataset for balloon borne samples by an order of magnitude, and more than doubling the total available stratospheric data (including aircraft samples) published to date. The samples also cover a large ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 68 publications
3
64
0
Order By: Relevance
“…This effect had not been recognized for more than a decade since the early years of GC-IRMS measurements (Merritt et al, 1995) and thus has not been taken into account in many data sets of atmospheric δ 13 C-CH 4 reported in the meantime (e.g. Miller et al, 2002;Morimoto et al, 2006;Fisher et al, 2011;Röckmann et al, 2011;Umezawa et al, 2012a, b). Furthermore, because the Kr effect is system dependent and variable with time , applying plausible corrections to past data may not be feasible.…”
Section: Krypton Interference In Gc-irmsmentioning
confidence: 99%
“…This effect had not been recognized for more than a decade since the early years of GC-IRMS measurements (Merritt et al, 1995) and thus has not been taken into account in many data sets of atmospheric δ 13 C-CH 4 reported in the meantime (e.g. Miller et al, 2002;Morimoto et al, 2006;Fisher et al, 2011;Röckmann et al, 2011;Umezawa et al, 2012a, b). Furthermore, because the Kr effect is system dependent and variable with time , applying plausible corrections to past data may not be feasible.…”
Section: Krypton Interference In Gc-irmsmentioning
confidence: 99%
“…25 (Brenninkmeijer et al, 1995) studied the correlation of CO2, CH4 and CO mole fractions and their isotopic composition measurements, and found a high correlation between mole fractions and isotopic compositions. It was shown that the 13 C and 2 H isotopic composition of stratospheric CH4 is strongly correlated with its mole fractions (Röckmann et al, 2011) and similar findings were presented for N2O (Kaiser et al, 2006). A theoretical explanation to the tracer-tracer relations due to rapid mixing of air along isentropic surfaces in the stratosphere was presented by (Plumb, 2007).…”
Section: Introductionmentioning
confidence: 56%
“…Although the Tedlar bags perform slightly better than the MLF bags, both are satisfactory for CH4 measurements when considering its large gradient in the stratosphere (500-2000 ppb e.g. (Röckmann et al, 2011)). …”
Section: The Storage Test Results 20mentioning
confidence: 99%
See 2 more Smart Citations